2020
DOI: 10.1097/bot.0000000000001711
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction Is Associated With Greater Hazard of Early Reoperation After Internal Fixation of Displaced Femoral Neck Fractures in Adults 18–65 Years

Abstract: Objectives: To determine (1) which factors are associated with the choice to perform an open reduction and (2) by adjusting for these factors, if the choice of reduction method is associated with reoperation. Design: Retrospective cohort study with radiograph and chart review. Setting: Twelve Level 1 North American trauma centers. Patients: Two hundred thirty-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
0
28
2
Order By: Relevance
“…One of the authors of the present study has previous experience with dynamic hip screw surgery and the short learning curve. FNS uses a nail-in-nail combination to increase anti-rotation stability and overall biomechanical properties, and the FNS power bar is a percussion placement rather than rotational placement of a dynamic hip head nail, avoiding the secondary rotational displacement of the femoral head caused by rotational torque [ 17 ]. The CS method requires three screws to be parallel with one another and to be in an inverted triangle formation, and requires a higher spatial distribution of screws.…”
Section: Discussionmentioning
confidence: 99%
“…One of the authors of the present study has previous experience with dynamic hip screw surgery and the short learning curve. FNS uses a nail-in-nail combination to increase anti-rotation stability and overall biomechanical properties, and the FNS power bar is a percussion placement rather than rotational placement of a dynamic hip head nail, avoiding the secondary rotational displacement of the femoral head caused by rotational torque [ 17 ]. The CS method requires three screws to be parallel with one another and to be in an inverted triangle formation, and requires a higher spatial distribution of screws.…”
Section: Discussionmentioning
confidence: 99%
“…However, opponents of open reduction argue that opening the capsule increases the risk of AVN by potentially damaging the anterior vessels [4]. A recent retrospective cohort study of 274 patients under 65 years of age with displaced FNF demonstrated a 2.4-fold greater hazard of reoperation following open reduction due to a complication such as AVN or non-union [3]. In contrast, a recent meta-analysis including 21 studies comparing open versus closed reduction found no difference in the rates of AVN, non-union or total complications [4].…”
Section: Discussionmentioning
confidence: 99%
“…Similar techniques have also been demonstrated for evaluating the quality of reductions intra-operatively in the syndesmosis, calcaneus, distal humerus, and distal radius [7-11]. In young FNF, the single most important modifiable treatment variable in predicting positive clinical outcomes and reducing the risk of post-operative complication is the quality of FNF reduction [3]. The application of this imaging technology to evaluating FNF reduction intra-operatively enables the surgeon to utilize closed reduction techniques, limiting the risk of damage to vascular structures, while allowing for critical assessment of FNF reduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations